Hungary : Staff Report for the 2010 Article IV Consultation and Proposal for Post-Program Monitoring. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Hungary was severely affected by the crisis. The financial sector has remained resilient throughout the crisis. The Central Bank (MNB) paused in mid-2010 and has tightened interest rates by 50 basis points since November in response to a sharp rise in risk premia and higher headline inflation prints. The importance of addressing financial sector vulnerabilities is discussed. Executive Directors welcomed efforts to support distressed mortgage holders, as long as moral hazard and fiscal costs are contained. A medium-term framework was implemented.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet